Dari Barter ke Online Shop: Konvergensi Penggunaan Media di Masa Pandemi COVID-19 - Prahastiwi Utari; Eka Nada Shofa Alkhajar; Emi Widiyanti; Tanti Hermawati (Wahana, 2023)
The COVID-19 pandemic has brought difficulties in various sectors of life, one of which is in the economic field, especially regarding the existence of traditional market traders. The lack of visitors due to the large-scale restrictions on people’s movement and the fear of contracting COVID-19 when interacting with other traders or buyers make the lives of traditional market traders more complicated and slumped. Indo Barter Community is a community that conducts a bartering process with traditional market traders to help them meet their daily needs. The bartering process is not only done conventionally using direct communication but also using digital media. Recording the entry and exit of goods, determining the selling price, and managing the payment system are done through a computerized program. In addition, the Indo Barter community also re-markets the barter results through WhatsApp and Instagram. The increasing customer demand has led the Indo Barter community to expand the market into an online shop.